2018
DOI: 10.1111/jog.13885
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional phase II study of neoadjuvant irinotecan and nedaplatin followed by radical hysterectomy and the adjuvant chemotherapy for locally advanced, bulky uterine cervical cancer: A Kansai Clinical Oncology Group study (KCOG‐G1201)

Abstract: Aim: A multi-institutional phase II trial was conducted to determine the efficacy and toxicity of neoadjuvant chemotherapy with irinotecan and nedaplatin followed by radical hysterectomy and adjuvant chemotherapy for locally advanced, bulky stage IB2-IIB cervical cancer. Methods: Patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB2-II, bulky type (>4 cm in diameter) squamous cell carcinoma of the uterine cervix were enrolled. Irinotecan (60 mg/ m 2 ) was administered intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…However, patients who accepted BOMP (cisplatin, vincristine, bleomycin, mitomycin) regimen in the phase III clinical trial-JCOG0102 showed 66% overall response, 41% severe leukopenia, and 27% severe thrombocytopenia (18). In a recent phase II clinical trial, Mori et al (28) evaluated the efficacy of irinotecan combined with nedaplatin in neoadjuvant chemotherapy: with 81.2% overall clinical response, the incidence of severe leukopenia was as high as 40.7%. Therefore, TP/TC regimen is with high response and rare adverse reaction, which is superior to other regimens for neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients who accepted BOMP (cisplatin, vincristine, bleomycin, mitomycin) regimen in the phase III clinical trial-JCOG0102 showed 66% overall response, 41% severe leukopenia, and 27% severe thrombocytopenia (18). In a recent phase II clinical trial, Mori et al (28) evaluated the efficacy of irinotecan combined with nedaplatin in neoadjuvant chemotherapy: with 81.2% overall clinical response, the incidence of severe leukopenia was as high as 40.7%. Therefore, TP/TC regimen is with high response and rare adverse reaction, which is superior to other regimens for neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent phase II clinical trial, Mori et al. ( 28 ) evaluated the efficacy of irinotecan combined with nedaplatin in neoadjuvant chemotherapy: with 81.2% overall clinical response, the incidence of severe leukopenia was as high as 40.7%. Therefore, TP/TC regimen is with high response and rare adverse reaction, which is superior to other regimens for neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Takekuma et al reported that chemotherapy after surgery for high-risk patients had similar e cacy and a different toxicity pro le from that of CCRT, associated with worse toxicity than chemotherapy [9]. In Japan, phase II trials have been conducted to determine the e cacy and toxicity of neoadjuvant chemotherapy (NAC) with irinotecan (CPT-11) and nedaplatin (NDP) followed by radical hysterectomy and adjuvant chemotherapy for locally advanced, bulky stage IB2-IIB cervical cancer [10][11][12][13].…”
Section: The National Comprehensive Cancer Network Guideline and The mentioning
confidence: 99%
“…Takekuma et al reported that chemotherapy after surgery for high-risk patients had a similar efficacy but a different toxicity profile than that of CCRT, which is associated with worse toxicity than chemotherapy [ 9 ]. In Japan, phase II trials have been conducted to determine the efficacy and toxicity of neoadjuvant chemotherapy (NAC) with irinotecan (CPT-11) and nedaplatin (NDP) followed by radical hysterectomy and adjuvant chemotherapy for locally advanced, bulky stage IB2-IIB cervical cancer [ 10 13 ]. Postoperative chemotherapy with CPT-11 and NDP without radiotherapy was also found to be very effective in high-risk patients with node-positive cervical cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%